Not the pacing site but the underlying structural heart disease is a reason for wider QRS duration during right ventricular pacing. (25th November 2020) - Ogano, M; Tsuboi, I; Tanabe, J; Iwasaki, Y; Shimizu, W
Abstract: Background: Right ventricular (RV) pacing causes changes of the electrical and mechanical activation pattern of the heart. QRS duration is reported to be a useful surrogate marker of electrical dyssynchrony, and wider QRS duration during RV pacing indicates poor prognosis. However, the mechanism of widening QRS duration during RV pacing remains to be elucidated. Methods: A total of 211 patients who underwent catheter ablation for supraventricular tachyarrhythmias and have no bundle-branch-block on ECG were enrolled. During electrophysiological study, 3-dimensional mapping for QRS duration during RV pacing from RV outflow to RV apex was created, and the difference of QRS duration between RV outflow and RV apex was calculated. The relationship between QRS duration during RV pacing and patients' baseline characteristics including echocardiography data was analyzed. Results: QRS duration at baseline, during RV pacing from RV outflow, and RV apex were 85.0±7.5msec, 156.2±16.1msec, and 163.7±17.1msec, respectively. The difference of QRS duration between RV outflow and RV apex among patients was only 12.5±10.4msec. The logistic multivariable regression analysis showed baseline QRS duration (odds ratio (OR) 1.24, 95% CI 1.15 to 1.34, p<0.01), interventricular septum thickness (OR 1.35, 95% CI 1.05 to 1.73, p=0.018), and E/e' (OR 1.23, 95% CI 1.12 to 1.36, p<0.01) were significant predictors for QRS duration over 160msec during RV apical pacing. Conclusions: QRS duration during RV pacing depends largely not on the pacing site, but on the underlying structural heart disease. Funding Acknowledgement: Type of funding source: None